KESIAPAN INFRASTRUKTUR TEKNOLOGI INFORMASI DALAM MENDUKUNG TRANFORMASI DIGITAL DI SEKOLAH DASAR - Paska Juan Tsunami; Ahmad Hariandi; Muhammad Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the readiness of information technology infrastructure to support digital transformation at SDN 13/I Muara Bulian based on three main stages, namely planning, implementation and evaluation. The research uses a qualitative approach with a case study design. Data was collected through observation, interviews and documentation studies, then analyzed interactively. The research results show that in the planning aspect, schools have basic plans for the provision of ICT infrastructure, although they are still limited by budget availability. In the implementation aspect, the use of information technology infrastructure has been implemented in learning activities and is supported by teacher readiness, but still faces device and network limitations. Meanwhile, in the evaluation aspect, the assessment of ICT infrastructure is still carried out in a simple and unstructured manner. This research concludes that the readiness of information technology infrastructure at SDN 13/I Muara Bulian is in the quite ready category, but requires strengthening planning, optimizing implementation, and more systematic evaluation so that digital transformation can run sustainably.